Spain : Financial Sector Assessment Program; Technical Note; Housing Prices, Household Debt, and Financial Stability. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This report reviews the macroeconomic determinants of the rapid growth in the Spanish housing market, including various policy elements. It examines the vulnerabilities of households' finances as a result of the rapid growth of housing prices and mortgage debt. It also describes the Spanish mortgage market and assesses the resilience of the financial sector to a possible adjustment in the housing and mortgage markets. It presents a market-based indicator to show the market views on the quality of the mortgage portfolio and also provides recommendations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet